Synthesis by free radical polymerization and properties of BN-polystyrene and BN-poly(vinylbiphenyl). Issue 93 (4th November 2016) - Wan, Wen-Ming; Baggett, Andrew W.; Cheng, Fei; Lin, Huina; Liu, Shih-Yuan; Jäkle, Frieder
Abstract : Free radical polymerization of B -vinyl- and B -styryl-functionalized azaborinine monomers gives organic–inorganic hybrid polymers with distinctly different materials properties compared to the corresponding carbonaceous polystyrene derivatives. Abstract : Free radical polymerization of B -vinyl- and B -styryl-functionalized azaborinine monomers gives well-defined hybrid polymers that were fully characterized by multinuclear NMR and GPC analysis; their solubility, thermal characteristics, and photophysical properties are dramatically different from those of the all-carbon polystyrene analogues.